The remembering self construction and accuracy in the self-narrative - Neisser, Ulric 1928-2012; Fivush, Robyn ca. 20./21. Jh (Emory symposia in cognition, 1994)
This book brings a surprisingly wide range of intellectual disciplines to bear on the self-narrative and the self. The same ecological/cognitive approach that successfully organized Ulric Neisser's earlier volume on The Perceived Self now relates ideas from the experimental, developmental, and clinical study of memory to insights from post-modernism and literature. Although autobiographical remembering is an essential way of giving meaning to our lives, the memories we construct are never fully consistent and often simply wrong. In the first chapter, Neisser considers the so-called 'false memory syndrome' in this context; other contributors discuss the effects of amnesia, the development of remembering in childhood, the social construction of memory and its alleged self-servingness, and the contrast between literary and psychological models of the self. Jerome Bruner, Peggy Miller, Alan Baddeley, Kenneth Gergen and Daniel Albright are among the contributors to this unusual synthesis